A Conceptual Framework for the Industrial District Analysis: from Knowledge to Resources - Juan Ignacio Dalmau-Porta; José Luis Hervás- Oliver; Maria del Val Segarra-O\~na (European Regional Science Association (ERSA), 2003)
Traditional literature on Industrial Districts has remarked the social capital as a core key in the development process of a sustainable territorial competitive advantage. In that concept authors are allocated part of the externalities without being underpined by an integrating conceptual framework. Recent resource-base view and knowledge management theory, as well as intellectual capital approach, can all be use as a conceptual framework to allocate all the industrial district's special features in a more comprehensive and connected arena. We establish a conceptual framework by integrating different approaches and adapt all of them to specific industrial district case. Moreover, we adapt the SECI knowledge management model to the cluster case as a useful way to understand the tacit knowledge dissemination that occurs in the industrial district.
Keywords: 330